(untitled) (Fiep Bulletin - online, 2011)
This study addressed the quality of life in academic Course of Business of the Center for Education of Campos Gerais (CESCAGE) in the city of Ponta Grossa, evaluated by questionnaire WHOOQOL – bref in two separate series of that course (semester and 01 half 07). The sample was designed with 20 students from first semester and 16 students from the seventh semester and the results show that half of the 01 students have a quality of life significantly lower compared to 07 academic semester. In the comparison between the components of the same sample results indicate that half of the 07 students have a lower dispersion compared to the results obtained by students of the semester 01.